2023
DOI: 10.7150/ijbs.84613
|View full text |Cite
|
Sign up to set email alerts
|

VDAC2 malonylation participates in sepsis-induced myocardial dysfunction via mitochondrial-related ferroptosis

Han She,
Lei Tan,
Yuanlin Du
et al.

Abstract: Sepsis-induced myocardial dysfunction (SIMD) is a prevalent and severe form of organ dysfunction with elusive underlying mechanisms and limited treatment options. In this study, the cecal ligation and puncture and lipopolysaccharide (LPS) were used to reproduce sepsis model in vitro and vivo. The level of voltage-dependent anion channel 2 (VDAC2) malonylation and myocardial malonyl-CoA were detected by mass spectrometry and LC-MS-based metabolomics. Role of VDAC2 malonylation on cardiomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…45 Malonylation of VDAC2 may induce mitochondrial dysfunction, increase mitochondrial ROS levels, lead to cell iron death, and inhibit tumor development. 46 The present study found that VDAC2 knockdown increased the resistance of cells to erastin-induced iron death, suggesting that VDAC2 silencing could indeed increase cell resistance to iron death, therebt promoting tumor development. In addition, rescue experiments showed that VDAC2 could reduce the cancer-promoting effect induced by TRIM8.…”
Section: Overexpression Of Vdac2 Reversed the Phenotype Of Oc Cells A...supporting
confidence: 50%
See 1 more Smart Citation
“…45 Malonylation of VDAC2 may induce mitochondrial dysfunction, increase mitochondrial ROS levels, lead to cell iron death, and inhibit tumor development. 46 The present study found that VDAC2 knockdown increased the resistance of cells to erastin-induced iron death, suggesting that VDAC2 silencing could indeed increase cell resistance to iron death, therebt promoting tumor development. In addition, rescue experiments showed that VDAC2 could reduce the cancer-promoting effect induced by TRIM8.…”
Section: Overexpression Of Vdac2 Reversed the Phenotype Of Oc Cells A...supporting
confidence: 50%
“…In addition, VDAC2 activation plays a key role in iron death, and knockdown of VDAC2 can increase cell resistance to iron death 45 . Malonylation of VDAC2 may induce mitochondrial dysfunction, increase mitochondrial ROS levels, lead to cell iron death, and inhibit tumor development 46 . The present study found that VDAC2 knockdown increased the resistance of cells to erastin‐induced iron death, suggesting that VDAC2 silencing could indeed increase cell resistance to iron death, therebt promoting tumor development.…”
Section: Discussionmentioning
confidence: 52%
“…4 D). Previous studies have shown that VDAC2 is involved in the regulation of mitochondria-related ferroptosis, mitochondrial ROS level and BAX-mediated apoptosis for limiting tumor development [46] , [47] . These could be well matched with the biological processes and functions of VDAC2, suggesting that Cel binding to VDAC2 induces ferroptosis and apoptosis in hepatic cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Sepsis represents a critical global health challenge, contributing significantly to the worldwide burden of morbidity and mortality. The Global Burden of Disease Study reports that in 2020, sepsis accounted for approximately 48.9 million incidences and 11 million fatalities across the globe 1 . Factors such as a burgeoning elderly population, the escalation of chronic disease prevalence, and a surge in antibiotic resistance have been implicated in the rising incidence of sepsis 2 .…”
Section: Introductionmentioning
confidence: 99%